2011
DOI: 10.3724/sp.j.1263.2011.00015
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the etiology of heart failure: A systematic review

Abstract: BackgroundHeart failure (HF) is an increasing problem for the aging population, specifically among women. The etiology of HF influences both the selection and outcome of the treatment. There are variations between genders in morbidity and mortality in different studies, possibly reflecting etiology. The objective of this study was to examine the strength of evidence available for gender differences in the etiology of chronic heart failure.MethodsComputer-assisted searches from 1980–2009 for gender differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 39 publications
(40 reference statements)
1
11
0
Order By: Relevance
“…The present study also showed no significant association between female sex and LVSD. This finding may be related to the fact that in women, LVD tends to be related to hypertension and DM and associated with preserved EF, whereas in men, it is more likely to be provoked by myocardial infarction [ 21 ]. Our research also showed that age >65 years is a risk factor for developing AS and diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The present study also showed no significant association between female sex and LVSD. This finding may be related to the fact that in women, LVD tends to be related to hypertension and DM and associated with preserved EF, whereas in men, it is more likely to be provoked by myocardial infarction [ 21 ]. Our research also showed that age >65 years is a risk factor for developing AS and diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Females with heart failure have more frequently a preserved left ventricular ejection fraction than men [6, 16], and they also tend to be older. However, as the purpose of this study was to analyze the efficacy and safety of SV in HFrEF, patients with preserved or mid-range ejection fraction were not included.…”
Section: Discussionmentioning
confidence: 99%
“…The systolic HF occurs when the heart does not pump vigorously to push enough blood into the body due to abnormal contraction of the ventricle. The ventricular systolic dysfunction is more common in males, whereas females are more associated with preserved left ventricular function [4].…”
Section: Introductionmentioning
confidence: 99%